Application of Economy Tokens to Reduce Gadgets Addiction to Children - Grace Latuheru; Tatik Meiyutariningsih (Proceedings of The ICECRS, 2020)
In the era of globalization, one of the effects of globalization is that the rapid technological development makes it easy for everyone to access all kinds of information through gadgets. Gadgets that initially made it easy for everyone will turn into a negative thing if you can not control yourself to use it, design with interesting features that might make someone want to linger to use it to feel dependent on the gadget. This research aims to reduce gadget addiction behavior in children. The research method is an experimental method with a case study approach is to provide Economy Tokens in order to control the behavior of children so they do not play gadgets for a long time. The token economy is given for 3 weeks and subjects must collect 5 stickers each week and then they will be exchanged for gifts in the form of toys they want. The subject is a child who is 7 years old in Ambon. Based on the analysis it can be concluded that the application of token economy can reduce gadget addiction in children. The subject's behavior is more controlled and is responsible for the decisions taken and their consequences. Another impact is the subject has good social interaction with people around him.